Pengembangan Usaha Koperasi Agar Dapat Mengenal Pasar dan Pesaing (International Forum of Researchers and Lecturers, 2025)
Strengthening the position of cooperatives as business entities that are responsive to market changes and capable of competing effectively requires a well-planned business development strategy. In facing the challenges of globalization and increasingly complex business competition, cooperatives can no longer rely solely on the principle of togetherness but must implement a modern managerial approach based on data and measurable strategies. This study aims to analyze how cooperatives develop their businesses by understanding market characteristics and competitor strategies through the application of operations management using the Balanced Scorecard (BSC) framework. The method used is a literature review with a qualitative descriptive approach, focusing on analyzing various literatures related to cooperative management, strategic management, and organizational performance measurement systems. The findings show that the Balanced Scorecard is effective as a tool to assist in formulating comprehensive strategies through four main dimensions: financial, customer, internal process, and learning and growth. With this approach, cooperatives can improve operational performance, gain deeper insights into market needs, respond appropriately to competition, and create long-term value for all their members.